2020
DOI: 10.1128/aac.02003-19
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Is Protective in a Neonatal Mouse Model ofStaphylococcus epidermidis-Potentiated Hypoxic-Ischemic Brain Injury

Abstract: Infection is correlated with increased risk of neurodevelopmental sequelae in preterm infants. In modeling neonatal brain injury, Toll-like receptor agonists have often been used to mimic infections and induce inflammation. Using the most common cause of bacteremia in preterm infants, Staphylococcus epidermidis, we present a more clinically relevant neonatal mouse model that addresses the combined effects of bacterial infection together with subsequent hypoxic-ischemic brain insult. Currently, there is no neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…We and others have demonstrated that synthetic compounds, such as Pam 3 CSK 4 , a Toll-like receptor (TLR) 2 agonist that mimics aspects of inflammation driven by Grampositive bacteria, increases the vulnerability of the brain to subsequent HI in neonatal mice (12,13). Recently we extended these findings to show that live S. epidermidis bacterial infection induced 14 h prior to HI also sensitizes the brain to increased injury (14). However, the time interval between infection and subsequent HI is known to be important in experimental studies (15).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…We and others have demonstrated that synthetic compounds, such as Pam 3 CSK 4 , a Toll-like receptor (TLR) 2 agonist that mimics aspects of inflammation driven by Grampositive bacteria, increases the vulnerability of the brain to subsequent HI in neonatal mice (12,13). Recently we extended these findings to show that live S. epidermidis bacterial infection induced 14 h prior to HI also sensitizes the brain to increased injury (14). However, the time interval between infection and subsequent HI is known to be important in experimental studies (15).…”
Section: Introductionmentioning
confidence: 84%
“…We have previously shown that S epidermidis infection can increase the vulnerability of the developing brain to HI (14). To evaluate the potentiation of brain injury after S. epidermidis infection over time, mice were subjected to a combination of S. epidermidis infection and HI.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations